On locally nilpotent derivations of Fermat rings - Brumatti, P.; Veloso, M. (Algebra and Discrete Mathematics, 2013)
In this note we prove that the ring B²n has non-zero irreducible locally nilpotent derivations, which are explicitly presented, and that its ML-invariant is C.